Hypertension-focused exercise on blood pressure management among Indonesian patients - Widiastuti, Widiastuti; Rahayu, Nofita (Universitas Muhammadiyah Magelang, 2025)
Hypertension remains a serious clinical condition globally that significantly contributing to fatalities worldwide. Intensive and comprehensive care is crucial for preventing its complications. While standard care is always necessary, its effectiveness can be optimized by integrating complementary therapies, such as hypertension management exercise. However, there are limited studies describing the effectiveness of this specific therapy within the Indonesian population. The purpose of this study was to ascertain whether hypertension exercise can lower blood pressure in hypertensive patients at at Turots Al Islamy Hospital, Yogyakarta, Indonesia. The study employed a quasi-experimental design with a one-group pretest-posttest research design. A total of 44 respondents were selected using purposive sampling. For the intervention, researchers utilized videos and leaflets as research instruments. The exercise sessions lasted 15-20 minutes, performed three times a week for two consecutive weeks. Ethical clearance was obtained before the study commenced. Data analysis involved descriptive statistics, normality tests, and the Wilcoxon test. The study found that hypertension exercise was effective in reducing hypertension, with an average reduction of 15.49 mmHg in systolic pressure and 8.19 mmHg in diastolic pressure. The findings of this study can be valuable for healthcare professionals, offering an innovative approach to hypertension management in both hospital and community practice, thereby enhancing chronic illness care. Keywords: Chronic illness, exercise, healthcare professionals, hypertension, innovation in care